Research Article Properties of The Water-Based Paint Mixed With The Purple Bacteria - et.al, Byungcheol Choi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, as carbon dioxide emission increases, global warming is rapidly progressing, and indoor air quality is also affected. In this study, a functional paint was prepared by mixing purple bacteria in an water-based paint, and carbon dioxide adsorption, alkali resistance, and impact resistance were tested. The mixing ratio of purple bacteria is set to 0, 5, 10, 15 (%), and the carbon dioxide adsorption experiment is divided into the case of no light and the case of light. As a result, In the absence of light, complete sealing is achieved as the carbon dioxide concentration in the empty chamber according to the mixing ratio of purple bacteria is considered to be kept constant as 100%. The carbon dioxide concentration of the paint without the purple bacteria was higher than that of the purple bacteria. In the case of light, the decrease of the carbon dioxide concentration tended to be more active than in the case of no light. There was no difference in alkali resistance and impact resistance when comparing the paint without the purple bacteria and the paint mixed with it. In addition, there was no difference even when the incorporation rate of purple bacteria increased. Finally, as for the viscosity, the faster the fall time of the paint, the lower the viscosity of the paint, and the drying time, the lower the viscosity of the paint, the longer the drying time. Therefore, It is believed that water-based paints mixed with purple bacteria can improve indoor air quality by adsorbing carbon dioxide.